Pengaruh Burnout, Work Life Balance Dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Karyawan - Reni Dwi Andrianti; Udik Jatmiko; Nur Hidayati (Jurnal Mahasiswa Kreatif, 2023)
This study aims to determine whether there is an influence of burnout, work life balance, and non-physical work environment on employee job satisfaction at PT Idea Global Indo. This research uses quantitative methods with non-probability sampling techniques with purposive sampling methods. The number of polulations was 40 employees and a sample of 32 staff. The analysis technique used is the research instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R2 ) which is processed using the SPSS software program version 25.0. Based on the results of the study, it is concluded that partially burnout does not have a significant effect on employee job satisfaction obtained Sig. 0.425> 0.05 with a tcount value < ttabel , namely -0.809 < 2.048. The work life balance variable partially has a significant effect on employee job satisfaction obtained Sig value. 0.032 ttabel value, namely 2.255> 2.048. Non-physical work environment variables partially have a significant effect on employee job satisfaction obtained Sig value. 0.001 ttabel value, namely 3.731> 2.293. Burnout, work life balance, and non-physical work environment variables simultaneously have a significant effect on employee job satisfaction obtained Sig value 0.001 < 0.05 with the value of Fcount > Ftabel which is 7,671 > 2.95.